Captain Underpants and the Big Bad Battle of the Bionic Booger Boy - Dav Pilkey
George and Harold thought they were beyond boogers. Their new pet, Sulu the Bionic Hamster, had defeated the Bionic Booger Boy, and through the wonders of science, Melvin Sneedly had been brought back to normal (well, almost normal). It looked like their last adventure was actually going to have a happy ending... except for one thing (well, three things) -- the Ridiculous Robo-Boogers. Now George, Harold, and their buddies are on the run -- with the Robo-Boogers in hot, gooey pursuit! Will the boys get away from these gross globs, or will Sulu have to save the day again?